(untitled) (Context: Journal of Interdisciplinary Studies, 2022)
This paper explores significant institutional and individual efforts in the struggle for the “authentic Rumi” among Muslims in the West, Turkey and Iran. Widely known in the Muslim world and among Orientalists for centuries, Rumi’s poetry became a global phenomenon in the 21st century. Free renditions by Coleman Barks have significantly contributed to Rumi’s new popularity. However, often accompanied by the erasure or minimisation of its Islamic content, the popular versions have met wide criticism in various Muslim contexts. Despite traditionally different approaches to Rumi’s poetry, the discourse about its “authentic interpretation” has become dominant in academia in Turkey and Iran, and among Muslim scholars in the West. Today, Muslim authors strongly emphasise the Islamic character of Rumi’s opus and call for the contextualization and reinterpretation of his poetry through the re-invention of traditional modes of its reading and understanding.